Zonal asymmetries in middle atmospheric ozone and water vapour derived from Odin satellite data 2001-2010 - Gabriel, A.; Körnich, H.; Lossow, S.; Peters, D.H.W.; Urban, J.; Murtagh, D. (Göttingen : Copernicus, 2011)
Stationary wave patterns in middle atmospheric ozone (O3) and water vapour (H2O) are an important factor in the atmospheric circulation, but there is a strong gap in diagnosing and understanding their configuration and origin. Based on Odin satellite data from 2001 to 2010 we investigate the stationary wave patterns in O3 and H2O as indicated by the seasonal long-term means of the zonally asymmetric components O3* Combining double low line O3-[O3] and H2O* Combining double low line H2O-[H2O] ([O3], [H2O]: zonal means). At mid-and polar latitudes we find a pronounced wave one pattern in both constituents. In the Northern Hemisphere, the wave patterns increase during autumn, maintain their strength during winter and decay during spring, with maximum amplitudes of about 10-20 % of the zonal mean values. During winter, the wave one in O3* shows a maximum over the North Pacific/Aleutians and a minimum over the North Atlantic/Northern Europe and a double-peak structure with enhanced amplitude in the lower and in the upper stratosphere. The wave one in H2O* extends from the lower stratosphere to the upper mesosphere with a westward shift in phase with increasing height including a jump in phase at upper stratosphere altitudes. In the Southern Hemisphere, similar wave patterns occur mainly during southern spring. By comparing the observed wave patterns in O 3* and H2O3* with a linear solution of a steady-state transport equation for a zonally asymmetric tracer component we find that these wave patterns are primarily due to zonally asymmetric transport by geostrophically balanced winds, which are derived from observed temperature profiles. In addition temperature-dependent photochemistry contributes substantially to the spatial structure of the wave pattern in O 3* . Further influences, e.g., zonal asymmetries in eddy mixing processes, are discussed.